PENGARUH KONTROL PEKERJAAN DAN PERILAKU AMAN TERHADAP KINERJA KARYAWAN PT. PERTAMINA HULU ENERGI ONWJ. - Subeno, Isni (Operations Excellence: Journal of Applied Industrial Engineering, 2014)
Abstract. This Research head for examine the control of work and safe behaviorto have influence on the performance. Dimension of them were taken from severalof sources. Sample was collected from PT. Pertamina Hulu Energi ONWJemployees, total sample of 86 respondents‘. Therespondents who working in theengineering Office and Offshore field operation range 35% and 65% from totallyof the sampling.The data was collected by the questionnaire filling. There have beenobtained are processed and result the correlation by using Method of SuccessiveInterval (MSI) and computer software SPSS (Statistical Product and ServiceSolution) versi 20. The core analysis by using Multiple linear regressionsThen thedatas annalized to find the correlation between them by the classic assumption testusing multikolinierity, heteroskedastisity, normality test and autocorrelation andthen hypothesis test by using koefisien determination (R²), partial statistic t (ttest), simultan statistic F (F test) and dimention correlation.The result of research indicated that variable of control of work and safebehavior have significant correlation with employee performace, and then bysimultantnously the control of work and the safe behavior have significantcorrelation with employee performace.Keywords: Control of Work, Safe behavior and Employee Performance.